Cardiac remodeling in patients with centrifugal left ventricular assist devices assessed by serial echocardiography. Issue 5 (7th April 2022) - Mulzer, Johanna; Krastev, Hristo; Hoermandinger, Christoph; Merke, Nicolas; Alhaloush, Mazen; Schoenrath, Felix; Falk, Volkmar; Potapov, Evgenij; Knierim, Jan
Abstract: Aim: The aim of the study was to characterize the remodeling process in a large cohort of patients supported with a centrifugal left ventricular assist device (cfLVAD) by standardized serial echocardiography. Methods and Results: From 3/2018 all cfLVAD patients underwent transthoracic echocardiography at 6 and 12 months after implantation using a standardized protocol. A total of 512 echocardiograms were reviewed (216 preoperative, 156 at 6 months, 140 at 12 months). While on cfLVAD support, left ventricular (LV) diameter decreased ( p  < .001). LV ejection fraction (LVEF) and LV fractional area change improved ( p  < .001). Potential for cfLVAD explantation (as defined by an LVEF ≥45% and opening of the aortic valve [AV]) was seen in nine patients at 6 and 21 patients at 12 months. The tricuspid annular excursion decreased significantly, while the right ventricular fractional area change did not change. Tricuspid regurgitation (TR) and mitral regurgitation (MR) improved significantly during LVAD support. Opening of the AV was seen in >64% of the patients at 6 months and in 66% at 12 months. Moderate aortic regurgitation (AR) was rare with 3.8% at 6 months but increased with the duration of cfLVAD support (8.5% at 12 months). We found no significant difference in echocardiographic parameters between patients supported with a HeartWare HVAD™ or a HeartMate 3™ device. Conclusion: LVAD therapy can lead to reverse LV remodeling and improvement of MR and TR. However, right ventricular function does not improve and prevalence of AR progressively increases during mechanical support.